Mobilisation of the Armies of the Polish – Lithuanian Commonwealth before the Battle of Pereyaslav in 1630 - Kovalets, Taras (Before the Battle, 2023)
This article outlines the mobilisation efforts made by both the Royal and the Hetman’s Chancellery with the aim of concentrating the maximum armed forces of the Crown army to suppress the uprising of the Zaporozhian Host under the command of Taras Fedorovych and Anton But. Particular aspects of the mobilisation were considered, such as the methodology of its implementation with regard to units of the so-called ‘quarter’ army (Polish: wojsko kwarciane), foreign troops, private cavalry banners, separate banners of the Lithuanian army, and the remnants of the Zaporozhian Host that remained loyal to the Commonwealth. Based on various published and archival sources (registers of army levies, official and private letters, narrative texts, etc.), the geography and chronology of the movement of the Commonwealth army units during this mobilisation, their composition, numbers, and the names of their commanders have been established as far as possible. Particular attention was paid to aspects of the mobilisation of the private cavalry banners of the local magnates from the Zbaraski, Zasławski-Ostrogski, and Zamoyski families, which have been little studied by historians so far, although soon after their mobilisation provided significant support for the quarter army. The beginning of the long and difficult mobilisation of a foreign regiment under the command of Jakub Butler and the Denhoff brothers and the preparation of the Crown artillery for the campaign are also discussed.The research also helped to conclude that after the first stages of mobilisation before the Battle of Pereyaslav, Field Crown Hetman Stanisław Koniecpolski had sufficient forces (in terms of quality and numbers) to stop the main part of the insurgents’ army and to attempt to engage the enemy in gruelling battles in open field.